Advanced Atomically Dispersed Metal–Nitrogen–Carbon Catalysts Toward Cathodic Oxygen Reduction in PEM Fuel Cells. Issue 37 (26th August 2021) - Deng, Yijie; Luo, Junming; Chi, Bin; Tang, Haibo; Li, Jing; Qiao, Xiaochang; Shen, Yijun; Yang, Yingjie; Jia, Chunman; Rao, Peng; Liao, Shijun; Tian, Xinlong
Abstract: Proton exchange membrane fuel cells (PEMFCs) are a highly efficient hydrogen energy conversion technology, which shows great potential in mitigating carbon emissions and the energy crisis. Currently, to accelerate the kinetics of the oxygen reduction reaction (ORR) required for PEMFCs, extensive utilization of expensive and rare platinum‐based catalysts are required at the cathodic side, impeding their large‐scale commercialization. In response to this issue, atomically dispersed metal–nitrogen–carbon (M–N–C) catalysts with cost‐effectiveness, encouraging activity, and unique advantages (e.g., homogeneous activity sites, high atom efficiency, and intrinsic activity) have been widely investigated. Considerable progress in this domain has been witnessed in the past decade. Herein, a comprehensive summary of recent development in atomically dispersed M–N–C catalysts for the ORR under acidic conditions and of their application in the membrane electrode assembly (MEA) of PEM fuel cells, are presented. The ORR mechanisms, composition, and operating principles of PEMFCs are introduced. Thereafter, atomically dispersed M–N–C catalysts towards improved acidic ORR and MEA performance is summarized in detail, and improvement strategies for MEA performance and stability are systematically analyzed. Finally, remaining challenges and significant research directions for design and development of high‐performance atomically dispersed M–N–C catalysts and MEA are discussed. Abstract : Recent developments in atomically dispersed metal–nitrogen–carbon (M–N–C) catalysts for the acidic oxygen reduction reaction and their application in the membrane electrode assembly (MEA) of proton exchange membrane fuel cells, are summarized. The improvement strategies for MEA performance and stability are analyzed and the remaining challenges and research directions that are expected to aid development of high‐performance atomically dispersed M–N–C catalysts and MEA are discussed.